2018
DOI: 10.1002/aenm.201703189
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Trimetallic NiFeCr Layered Double Hydroxide Electrocatalysts for Oxygen Evolution Reaction

Abstract: rechargeable metal-air batteries. [1,2] This reaction demands efficient electrocatalysts that can accelerate the reaction rate, lower the overpotential, and remain stable over time. Currently, noble-metal-based compounds such as IrO 2 and RuO 2 provide good OER performance under alkaline conditions, but their large-scale application is restricted by their scarcity and high cost. [3] Accordingly, much research effort has been devoted to the development of high-performance earth-abundant OER electrocatalysts ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
317
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(332 citation statements)
references
References 66 publications
14
317
0
1
Order By: Relevance
“…Thedouble layer capacitance (C dl ) values were obtained by measuring the change of current within apotential period without the Faradaic process,which can be represented by the plots of Dj = (ja-jc)/2 at 1.0744 V vs.RHE against the scan rate (Figure 3b). [28] TheN yquist plots revealed that the semicircular diameter of Ni-Fe-MOF NSs was smaller than that of XPS was carried out to understand the effect of mixed metals on OER catalysis.C ompared with the Ni-MOF NSs, the peaks of Ni 2p 3/2 and Ni 2p 1/2 in the high-resolution Ni 2p spectrum of the Ni-Fe-MOF NSs shifted to as lightly higher binding energy (a shift of approximately 0.3 eV), indicating amodified local electronic structure of Ni (Figure 3d). [28] TheN yquist plots revealed that the semicircular diameter of Ni-Fe-MOF NSs was smaller than that of XPS was carried out to understand the effect of mixed metals on OER catalysis.C ompared with the Ni-MOF NSs, the peaks of Ni 2p 3/2 and Ni 2p 1/2 in the high-resolution Ni 2p spectrum of the Ni-Fe-MOF NSs shifted to as lightly higher binding energy (a shift of approximately 0.3 eV), indicating amodified local electronic structure of Ni (Figure 3d).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thedouble layer capacitance (C dl ) values were obtained by measuring the change of current within apotential period without the Faradaic process,which can be represented by the plots of Dj = (ja-jc)/2 at 1.0744 V vs.RHE against the scan rate (Figure 3b). [28] TheN yquist plots revealed that the semicircular diameter of Ni-Fe-MOF NSs was smaller than that of XPS was carried out to understand the effect of mixed metals on OER catalysis.C ompared with the Ni-MOF NSs, the peaks of Ni 2p 3/2 and Ni 2p 1/2 in the high-resolution Ni 2p spectrum of the Ni-Fe-MOF NSs shifted to as lightly higher binding energy (a shift of approximately 0.3 eV), indicating amodified local electronic structure of Ni (Figure 3d). [28] TheN yquist plots revealed that the semicircular diameter of Ni-Fe-MOF NSs was smaller than that of XPS was carried out to understand the effect of mixed metals on OER catalysis.C ompared with the Ni-MOF NSs, the peaks of Ni 2p 3/2 and Ni 2p 1/2 in the high-resolution Ni 2p spectrum of the Ni-Fe-MOF NSs shifted to as lightly higher binding energy (a shift of approximately 0.3 eV), indicating amodified local electronic structure of Ni (Figure 3d).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…X‐ray diffraction (XRD) patterns of V‐NiOOH displayed a weak intensity of peaks compared to NiOOH (Figure c), implying that the defects or amorphous phase were existed in OEC after treatment. X‐band electron paramagnetic resonance (EPR) spectroscopy of V‐NiOOH showed a stronger g signal intensity than NiOOH (Figure f), indicative of the modulating effect of plasma etching on the electronic structure of NiOOH …”
Section: Figurementioning
confidence: 99%
“…Non-noble metal phosphides, [5] chalcogenides, [6] carbides, [7] nitrides [8] have been explored as electrocatalysts for HER in acidic media and metal oxides [9] or hydroxide [10] are widely investigated as OER catalysts in basic media. Although these HER and OER electrocatalysts often function well in acidic or alkaline solutions, respectively, it is difficult to couple HER and OER catalysts in an integrated electrolyzer in the same electrolyte with good overall water splitting performance because of the incompatibility between stability and activity.…”
Section: Introductionmentioning
confidence: 99%